2019
DOI: 10.1016/j.neuropsychologia.2018.12.013
|View full text |Cite
|
Sign up to set email alerts
|

Self-perspective in episodic memory after parietal damage and in healthy ageing

Abstract: If citing, it is advised that you check and use the publisher's definitive version for pagination, volume/issue, and date of publication details. And where the final published version is provided on the Research Portal, if citing you are again advised to check the publisher's website for any subsequent corrections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 62 publications
1
24
0
Order By: Relevance
“…The retrieval of autobiographical and word-pair memories differs in that the former often involves the subjective experience of remembering multifaceted events that take place over a sequence of phases, combining features that may be of several modalities and recalled from a first-person point-of-view [51][52][53]. Accordingly, AG has been found to be differentially sensitive to the retrieval of multi-modal spatio-temporal memories compared to those involving only a single sensory modality [54][55][56][57], and to integrate these features within an egocentric perspective [47,58], in a way that is characteristic of true episodic memory [59].…”
Section: Insert Figure 1 About Herementioning
confidence: 99%
“…The retrieval of autobiographical and word-pair memories differs in that the former often involves the subjective experience of remembering multifaceted events that take place over a sequence of phases, combining features that may be of several modalities and recalled from a first-person point-of-view [51][52][53]. Accordingly, AG has been found to be differentially sensitive to the retrieval of multi-modal spatio-temporal memories compared to those involving only a single sensory modality [54][55][56][57], and to integrate these features within an egocentric perspective [47,58], in a way that is characteristic of true episodic memory [59].…”
Section: Insert Figure 1 About Herementioning
confidence: 99%
“…Although this was interpreted as an impairment of subjective memory in these patients, a reduction in their objective memory for the perceptual details of these recollections, although not tested, may also explain this effect. Of note, Russell et al 56 recently reported that individuals with right hemisphere IPL damage and without unilateral hemispatial neglect symptoms were specifically impaired in recalling their self-perspective at encoding. Contrastingly, these individuals could recall other information about the episode that could be summarised with a label 56 , potentially enabling functional compensation by the left hemisphere's IPL.…”
Section: Discussionmentioning
confidence: 99%
“… 56 recently reported that individuals with right hemisphere IPL damage and without unilateral hemispatial neglect symptoms were specifically impaired in recalling their self-perspective at encoding. Contrastingly, these individuals could recall other information about the episode that could be summarised with a label 56 , potentially enabling functional compensation by the left hemisphere’s IPL. These studies all suggest that perceptual feature information is more susceptible than semantic/conceptual information to memory impairment when IPL function is compromised.…”
Section: Discussionmentioning
confidence: 99%
“…Other research has tested whether angular gyrus is also important for imbuing memories with the characteristic of first-person perspective that Wordsworth evoked so powerfully [8,14,15]. For example, when volunteers were asked to recall autobiographical memories from their personal pasts, participants reported fewer of their memories as being experienced from a first-person perspective following angular gyrus disruption induced by brain stimulation compared with stimulation of a control brain region [8].…”
Section: The Subjective Experience Of Rememberingmentioning
confidence: 99%